Determinants of diagnostic and pseudodiagnostic information selection - Tsiourpas, Markellos; Vallee - Tourangeau, Frederic; Kordoutis, Panagiotis (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Pseudodiagnosticity refers to the tendency to select impoverished information in preference to equally available diagnostic data. Mynatt, Doherty, and Dragan (1993) reported that pseudodiagnostic reasoning was attenuated in problems in which the information selection had consequences for the reasoner’s future actions in contrast to problems in which it did not. Girotto, Evans and Legrenzi (1996) denied that such “action” problems fostered better information selection because they argued that in Mynatt’s et al.’s study action and non-action or inference varied in how the decision task was framed. It was predicted that for action problems there will be a higher frequency in informative data selection vs. both inference problems. In addition to that, a primacy effect for inference problems would occur irrespective of sequence of data presentation but not for action problems. We re-examined the way people reasoned about action problems and inference problems taking into consideration Girotto et al.’s criticisms. We found that even when the presentation and salience of the information was equated in both kinds of problems, diagnostic information selection was more likely for action that for inference problems.